Euphopubescenol and euphopubescene, two new jatrophane polyesters, and lathyrane-type diterpenes from Euphorbia pubescens - Valente, C (2015)
The structures of euphopubescenol and euphopubescene, two new macrocyclic jatrophane diterpene polyesters, isolated from the whole dried plant of Euphorbia pubescens, were established as 5alpha,8alpha,15beta-triacetoxy-3alpha-benzoyloxy-4alpha-hydroxy-9,14-dioxo-13betaH-jatropha-6(17),11E-diene (1) and 3beta,7beta,8beta,9alpha,14alpha,15beta-hexa-acetoxy-2betaH-jatropha-5E,11E-diene (2) by 1D- and 2D-NMR (COSY, HMQC, HMBC and NOESY), IR, EI-MS and EI-FTICR-MS. Two known lathyrane derivatives, jolkinol A (3) and jolkinol A (4), whose C-13-NMR spectra were assigned, were also isolated. Compounds 1-3 have been evaluated for their ability to inhibit the in vitro growth of three human tumour cell lines representing different tumour types, MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and SF-268 (CNS cancer). They inhibited both MCF-7 and NCI-H460 cell lines, with GI(50) values ranging between 40.9 muM and 95.3 muM, but were found to be ineffective as growth inhibitors of the SF-268 cell line.